Influence of MTHFR gene polymorphism C677T on the risk of recurrent spontaneous abortions (Uticaj polimorfizma C677T gena za MTHFR na nastanak spontanih pobačaja) - Svirčev, Miloš; Maksimović, Nela (Medicinski podmladak, 2018)
ABSTRACT Introduction: Spontaneous abortion (SA) is a frequent obstetric complication. Up to 20% of pregnancies end by spontaneous abortion in the first trimester. Five percent of women have two, and 1-2% of women have more than three abortions. The risk of spontaneous abortions is influenced by variety of genetic and environmental factors. Enzyme methylenetetrahydrofolatereductase (MTHFR) is primarily involved in homocysteine remethylation to the methionine. Gene polymorphism C677T in the MTHFR gene causes enzyme thermolability which leads to hyperhomocysteinemia, that increases the risk of developing deep vein thrombosis. Pregnancy predisposes the development of vein thrombosis that can lead to spontaneous abortions and other complications. The Aim: The aim of our study was to determine whether the MTHFR C677T polymorphism is associated with increased risk of SA. Material and methods: This study included 157 women who had at least two unexplained spontaneous abortions and 135 healthy controls without previous SA. Detection of MTHFR C677T polymorphism genotypes was performed by PCR-RFLPs method. Investigation of differences between genotype and allele frequencies in the group of women with SA and the control group was completed using the χ2 test. Results: In the group of patients with recurrent spontaneous abortions 58 (36.94%) had CC genotype, 74 (47.13%) CT genotype, and 25 (15.92%) TT genotype. In the control group consisting of 135 female patients, 59 (43.07%) had CC genotype, 55 (40.74%) CT genotype, and 15.56% TT genotype. The frequency of C allele in the group of patients was 60.51%, and T allele 39.49%; while the frequencies in the control group were 64.07% and 35.93%, respectively. The difference in the genotype (p=0.470) and allele (p=0.393) frequency between the two groups of patients was statistically insignificant. Conclusion: Our results do not show any influence of the analyzed polymorphism on SA. Keywords: MTHFR C677T polymorphism, spontaneous abortion SAŽETAK Uvod: Spontani pobačaj predstavlja čestu komplikaciju u akušerstvu. Oko 15 % trudnoća završi se spontanim pobačajem u prvom trimestru. Kod 5% žena javlja se dva, a kod 1-2% više od tri spontana pobačaja. Brojni genetički faktori i faktori spoljašnje sredine mogu biti uzrok spontanih pobačaja. Enzim metilen-tetrahidrofolat reduktaza (MTHFR) učestvuje u remetilaciji homocisteina do metionina. Polimorfizam C677T u genu za MTHFR dovodi do nastanka termolabilne forme enzima i pada enzimske aktivnosti što za posledicu ima hiperhomocisteinemiju, koja predstavlja rizik za nastanak dubokih venskih tromboza. Trudnoća predisponira ispoljavanje venske tromboze, koja dovodi do spontanih pobačaja i drugih komplikacija. Cilj rada: Cilj naše studije je da utvrdimo da li polimorfizam C677T predstavlja faktor rizika za nastanak spontanih pobačaja. Materijal i metode: Naša studija je obuhvatila 157 pacijentkinja koje su imale dva ili više spontana pobačaja i 135 zdrave žene koje nisu imale nijedan pobačaj. Polimorfizam C677T gena za MTHFR detektovan je uz pomoć PCR-RFLP metode. Razlika između učestalosti genotipova i alela u grupi žena sa spontanim pobačajima i u kontrolnoj grupi ispitivana je χ2 testom. Rezultati: U grupi pacijentkinja sa rekurentnim spontanim pobačajima, CC genotipa bilo je njih 58 (36,94%), CT genotipa 74 (47,13%) a TT genotipa 25 (15,92%). U kontrolnoj grupi CC genotipa bilo je njih 59 (43,70%), CT genotipa 55 (40,74%) a TT genotipa 21 (15,56%). Učestalost C alela u grupi pacijentkinja je 60,51%, a T alela 39,49% dok je u kontrolnoj grupi učestalost C alela 64,07%, a T alela 35,93%. Razlike u učestalosti genotipova (p=0.470) i alela (p=0.409) između grupe pacijentkinja i kontrolne grupe nisu bile statistički značajne. Zaključak: Naši rezultati ne ukazuju da bi analizirani polimorfizam mogao imati uticaja na nastanak spontanih pobačaja. Ključne reči: MTHFR C677T polimorfizam, spontani pobačaji